Prediction of the tensile strength of FDM specimens based on Tsai Hill criteria (Fracture and Structural Integrity, 2025)
This study investigates the mechanical behavior of 3D-printed polyethylene terephthalate glycol (PETG) polymer specimens subjected to tensile and shear testing, with a particular focus on the influence of raster orientation and shell contour. Specimens were fabricated using Fused Deposition Modeling (FDM) at three raster angles (0°, 45°, and 90°) and tested using both a mechanical extensometer and a Digital Image Correlation (DIC) system.The results indicate a significant influence of raster orientation on tensile and shear properties. 0° specimens exhibited the highest tensile strength, as the filament alignment was parallel to the loading direction. In contrast, 45° specimens demonstrated more ductile behavior. While the shell contour had minimal effect on 0° and 45° specimens, it enhanced stiffness and ductility in 90° specimens.Furthermore, the Tsai-Hill criterion was applied to predict the tensile strength at a 45° orientation.These findings contribute to a deeper understanding of the anisotropic behavior of 3D-printed materials and highlight the importance of raster orientation in optimizing mechanical performance.
Keywords: FDM; Tsai Hill criteria; PETG; DIC; Mechanical behaviour